Kualitas dan Interpretasi tentang Doa: Studi Takhrij dan Syarah Hadis - Imam Abdul Aziz; Tita Yuliawati (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about prayer. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of takhrij hadith, while the material object is the hadith about prayer in Abu Daud's narration No. 1313. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Abu Daud No. 1313 is relevant to be used as a guide in daily life.